GLOMERULONEPHRITIS: HIDDEN POVERTY IN THE KIDNEYS - Abdurakhmonova Gulsanam Dilkashovna; Tursunmetov Ibodulla (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Abstract: Glomerulonephritis (GN) is a disease characterized by the development of inflammatory processes in the renal glomeruli, which may lead to kidney failure. This article reviews the main causes, clinical symptoms, diagnostic methods, and treatment approaches for glomerulonephritis. The study analyzes the prevalence and clinical features of both acute and chronic forms of glomerulonephritis. It highlights the necessity for early detection of kidney diseases, the improvement of treatment methods, and the development of holistic approaches in local medical practice. Additionally, it was found that patients who frequently suffered from angina and dental infections during childhood have a higher risk of developing kidney diseases. The main goal is the early diagnosis of glomerulonephritis and the development of treatment strategies adapted to local conditions.